Association of Chronic Myelogenous (Basophilic) Leukemia and the BCR/ABL Mutation in a Yucatan Barrow (Sus scrofa domestica) - Takawira, Catherine; Arsuaga-Zorrilla, Carmen B.; Wilson, Leslie; Taguchi, Takashi; Dietrich, Marilyn A.; Stout, Rhett W.; Lopez, Mandi J. (Frontiers in Veterinary Science, 2020)
Background Chronic myelogenous leukemia (CML) is a clonal proliferative disorder of the myeloid, megakaryocyte, and erythroid lineages. The onset and subsequent progression of CML is well described in humans. There is comparably little information surrounding CML progression in veterinary species, including Yucatan miniature swine that are common for preclinical pharmaceutical and device testing. In humans, more than 90% of CML cases are associated with a chromosomal translocation that results in the Philadelphia gene (BCR/ABL mutation). In this report, the presence of the Philadelphia gene in a Yucatan burrow was confirmed in white blood cells collected prior to onset of clinical signs with primers designed from the human BCR/ABL sequence. Case Presentation A 24 month old, 70 kg, Yucatan barrow received a prefabricated bovine cortical bone xenograft following a unilateral zygomatic ostectomy for a preclinical study. Complete blood count and serum chemistries were performed prior to and 28, 53, 106, and 129 days after facial surgery. Fifty three days after surgery, a bone marrow biopsy was performed due to anorexia, severe basophilia, and mild anemia. A finding of a moderate increase in basophilic precursors in bone marrow cytology was followed by lymphocyte immunophenotyping via flow cytometry and RT-PCR amplification of the Philadelphia gene in white blood cell samples from the affected barrow and an unaffected barrow in the same treatment group. Bone marrow, lymph node, liver, spleen, lung, kidney and adrenal gland lesions of mostly myeloblasts were identified after the affected barrow died 146 days after surgery. Flow cytometry confirmed lymphopenia and suggested basophilia, and RT-PCR established the presence of the BCR/ABL gene. Conclusions The information in this report confirms the presence of the BCR/ABL mutation and documents progression of chronic myelogenous (basophilic) leukemia from a chronic phase to a terminal blast crisis in an adult Yucatan barrow. The natural occurrence and progression of CML associated with the BCR/ABL mutation in miniature swine establishes potential for future porcine models of human CML. The information also establishes a genetic test to confirm porcine CML to prevent inadvertent attribution of clinical signs to treatment complications during preclinical testing.